Text representation : linguistic and psycholinguistic aspects - Sanders, Ted; Schilperoord, Joost; Spooren, Wilbert (Human cognitive processing, 2001)
This book brings together linguistics and psycholinguistics. Text representation is considered a cognitive entity: a mental construct that plays a crucial role in both text production and text understanding. The focus is on referential and relational coherence and the role of linguistic characteristics as processing instructions from a text linguistic and discourse psychology point of view. Consequently, this book presents various research methodologies: linguistic analysis, text analysis, corpus linguistics, computational linguistics, argumentation analysis, and the experimental psycholinguis.